2022
DOI: 10.1259/bjr.20220634
|View full text |Cite
|
Sign up to set email alerts
|

Spleen size in homozygous sickle cell disease: trends in a birth cohort using ultrasound

Abstract: Objectives: To provide ultrasound baselines for spleen length in homozygous sickle cell disease (HbSS) and in normal controls with a HbAA genotype. Methods: The Jamaican cohort study identified 311 babies with HbSS and 246 matched HbAA controls during the screening of 100,000 consecutive deliveries in Kingston, Jamaica from 1973 to 1981. Ultrasonography commenced in 1988 when the youngest patients were aged 6 years at which time deaths, emigrations and default had reduced the numbers to 206 HbSS and 89 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In our study, the spleen was visualised on ultrasonography among all the children under 5 years, but declined in prevalence with successively older age groups, so that only about a quarter of patients had their spleens visualised on ultrasonography after the age of 15 years. A similar pattern was noted recently among a large Jamaican birth cohort of patients with SCD (n = 2138); non-visualised spleens increased with age from 34% in those aged 6.0-7.9 years to 72% in those aged 24 years and older [20]. In contrast, a study among SCD children in the United Kingdom (n = 100) showed that only 5.6% of children aged 6-10 years and 19.4% of children aged 11-16 years had no visible spleen on ultrasonography [21].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, the spleen was visualised on ultrasonography among all the children under 5 years, but declined in prevalence with successively older age groups, so that only about a quarter of patients had their spleens visualised on ultrasonography after the age of 15 years. A similar pattern was noted recently among a large Jamaican birth cohort of patients with SCD (n = 2138); non-visualised spleens increased with age from 34% in those aged 6.0-7.9 years to 72% in those aged 24 years and older [20]. In contrast, a study among SCD children in the United Kingdom (n = 100) showed that only 5.6% of children aged 6-10 years and 19.4% of children aged 11-16 years had no visible spleen on ultrasonography [21].…”
Section: Discussionsupporting
confidence: 86%
“…Lower frequencies have been found in Asia (11%) [33], the Middle-East (6.1%) [12] and the United States (9%) [21]. The variability of splenic nonvisualisation on ultrasonography in the different geographic location may partly be explained by the presence of genetic factors known to inhibit sickling, such as alphathalassaemia and HbF [11,20], improvement in clinical care and outcomes in SCD [21,32], and also environmental factors that results in the frequent exposure to organisms known to cause spleen enlargement including malaria and bacterial infections [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential weaknesses include the diligence of different doctors recording splenomegaly, difficulties of assessment in sometimes sick children and that clinical splenic enlargement imperfectly reflects spleen size on ultrasonography. 25 The prevalence of ASS in the Jamaican cohort at 35% exceeded the 10% reported from the cooperative study in the USA, 26 7% in western Saudi Arabia 27 and 16% in a French study. 15 All studies used similar definitions for ASS, and the greater frequency in the cohort may reflect clinically mild cases from auditing serial haematology, a hypothesis consistent with the relatively benign clinical course, 90 out of 183 (49%) events resolving without admission and 90 out of 183 (49%) without transfusion.…”
Section: Discussionmentioning
confidence: 62%
“…Following up children from birth created a novel challenge as the early establishment of haemolysis in HbSS, also qualified for the accepted diagnosis of ASS. Potential weaknesses include the diligence of different doctors recording splenomegaly, difficulties of assessment in sometimes sick children and that clinical splenic enlargement imperfectly reflects spleen size on ultrasonography 25. The prevalence of ASS in the Jamaican cohort at 35% exceeded the 10% reported from the cooperative study in the USA,26 7% in western Saudi Arabia27 and 16% in a French study 15.…”
Section: Discussionmentioning
confidence: 92%